(untitled) (Archives of Mechanics - Test, 1996)
A general formulation is proposed to treat the dynamic response of saturated soils in finite deformation regime. Considering the soil as a saturated porous medium, the formulation for finite deformation analysis was established by extending Biot’s classical theory to incorporate finite deformation effects. Particular attention was given to the flow of water through the soil while the soil skeleton undergoes a finite deformation. The derived formulation constitutes the theoretical basis for analysis of the liquefaction induced flow failure in soil embankments. Due to the integral form of the governing equations, they are specially suitable for application of numerical methods such as the finite element method.